Self-directed learning as related to learning strategies, self-regulation, and autonomy in an English language program: A local application with global implications - Williamson Hawkins, Melissa (Studies in Second Language Learning and Teaching, 2018)
English language tutoring and/or self-access centers are services commonly offered as curricular support to English language program students in educational environments worldwide. This paper argues that the theory of self-directed learning (SDL) from the field of adult education should be considered alongside the equally-important areas of language learning strategies, learner autonomy, and self-regulated learning in the setup of these types of tutoring/self-access academic support centers. The proposition is examined by applying it to a particular case in an English language program of a major research university in the southeastern United States. The paper explicates the commonly-known theory of SDL (Grow, 1991) and relates it to models by put forward by Nakata (2010) and Oxford (2011, 2107). Empirical evidence from studies on encouraging SDL for English language study is summarized from a range of research projects conducted worldwide, and the author concludes by offering implications for educators in any institution-based, adult English language program.